Terapêutica não medicamentosa para febre: tem validade? - Victor Lenon Aires Peixoto; Fernando de Almeida Machado (Residência Pediátrica)
INTRODUCTION: Fever is one of the most common complaints seen in a pediatric appointment. Although this, many physicians and parentes atitudes are taken soonly because they have too many misconceptions and concerns about fever. Among these attitudes, physical cooling methods are common. OBJECTIVES: the aim of this study is showing what is disseminated by medical literature about cooling methods in management of fever, its benefits and harms. METHODS: its a literature integrative review about non chemical management of fever. The authors searched the Medline trials register and a free search to find others studies not published in that digital platform with the question: Whats is the value of non chemical fever management? RESULTS: It was included 25 studies met the inclusion criteria. DISCUSSION: there are many conflicting results showing or not showing benefits in the fever management with physical methods. Much of them show benefits only in the first minuts after cooling. Several conflicting results must be due the methodological problems. CONCLUSIONS: Currently, there is no definitive answers about advantages and disadvantages in fever management by using physical methods, considering risk and benefits.